The Correlation of Self-Experience with Sex Education in Parents of Preschool-Aged Children In Paud Al-Irsyad Sumedang Regency - Nurwita, Ati; Mauliku, Novie E; Gantari, Indira (MEDIA ILMU KESEHATAN, 2023)
Background: Sex education for preschool is appropriate to prevent sexual violence. Teachers and parents can work together. But, one phenomenon from parents is taboo for given sex education to early childhood. Several factors that influence of implemented is perceptions of behavioral control. One thing that influences that is self-experience.Objective: The purpose of this study was to analysis correlation of self-experience and sex education in parents of preschool-aged children.Methods: The design of this study was observational analytic with a cross sectional approach. The population is 30 parents who have children aged 3-6 years in PAUD Al-Irsyad through total sampling. The research instrument used a primary data collection questionnaire. Data analysis was performed univariate and bivariate using the chi-square test. Results: The results showed that 56,7 %had provided sex education. The chi-square test showed p value 1,000 > ?= 0,050.Conclusion: There is no relationship between parents’ self-experience and the implementation of sex education in preschool. This can encourage further studies of other factors, so that dominant factors can be found that encourage parents to carry our early sex education.